(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
Тихий океан — уникальный по величине природный объект нашей планеты. Площадь водной поверхности Тихого океана составляет 178,7 млн км², что составляет более ⅓ поверхности планеты и почти ½ Мирового океана. Тихий океан расположен во всех полушариях: в Северном и в Южном по обе стороны от экватора и в Западном и в Восточном по отношению к 180-му меридиану. The Pacific Ocean is a unique natural object on our planet. The water surface area of ​​the Pacific Ocean is 178.7 million km², which is more than ⅓ of the planet's surface and almost ½ of the World Ocean. The Pacific Ocean is located in all hemispheres: in the Northern and Southern hemispheres on both sides of the equator and in the Western and Eastern hemispheres in relation to the 180th meridian.